Epithelial-myeloid exchange of MHC class II constrains immunity and microbiota composition - W. Zac Stephens (Elsevier, 2021)
Summary: Intestinal epithelial cells (IECs) have long been understood to express high levels of major histocompatibility complex class II (MHC class II) molecules but are not considered canonical antigen-presenting cells, and the impact of IEC-MHC class II signaling on gut homeostasis remains enigmatic. As IECs serve as the primary barrier between underlying host immune cells, we reasoned that IEC-intrinsic antigen presentation may play a role in responses toward the microbiota. Mice with an IEC-intrinsic deletion of MHC class II (IECΔMHC class II) are healthy but have fewer microbial-bound IgA, regulatory T cells (Tregs), and immune repertoire selection. This was associated with increased interindividual microbiota variation and altered proportions of two taxa in the ileum where MHC class II on IECs is highest. Intestinal mononuclear phagocytes (MNPs) have similar MHC class II transcription but less surface MHC class II and are capable of acquiring MHC class II from IECs. Thus, epithelial-myeloid interactions mediate development of adaptive responses to microbial antigens within the gastrointestinal tract.